An introduction to medicinal chemistry - Patrick, Graham L. (Oxford : Oxford University Press, 2013)
This volume provides an introduction to medicinal chemistry. It covers basic principles and background, and describes the general tactics and strategies involved in developing an effective drug.
Drugs and drug targets - an overview -- Drug targets : structure and function -- Protein structure and function -- Enzymes: structure and function -- Receptors: structure and function -- Receptors and signal transduction -- Nucleic acids: structure and function -- Pharmacodynamics and pharmacokinetics -- Enzymes as drug targets -- Receptors as drug targets -- Nucleic acids as drug targets -- Miscellaneous drug targets -- Pharmacokinetics and related topics -- Statins -- Drug discovery, design, and development -- Drug discovery: finding a lead -- Drug design: optimizing target interactions -- Drug design: optimizing access to the target -- Getting the drug to market -- The design of ACE inhibitors -- Artemisinin and related antimalarial drugs -- The design of oxamniquine -- Tools of the trade -- Combinatorial synthesis -- Computers in medicinal chemistry -- Quantitative structure-activity relationships (QSAR) -- De novo design of a thymidylate synthase inhibitor -- Selected topics in medicinal chemistry -- Antibacterial agents -- Antiviral agents -- Anticancer agents -- Cholinergics, anticholinergics, and anticholinesterases -- Drugs acting on the adrenergic nervous system -- Opioid analgesics -- Antiulcer agents -- Steroidal anti-inflammatory agents -- Design of a novel antidepressant.
Includes bibliographical references and index.
Keywords: Chemistry, Pharmaceutical; Drug Design; Pharmacokinetics; Pharmaceutical chemistry; Farmacochemie